2011
DOI: 10.1111/j.1740-0929.2011.00881.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation analysis on satellite I region in blastocysts obtained from somatic cell cloned cattle

Abstract: Many observations have been made on cloned embryos and on adult clones by somatic cell nuclear transfer (SCNT), but it is still unclear whether the progeny of cloned animals is presenting normal epigenetic status. Here, in order to accumulate the information for evaluating the normality of cloned cattle, we analyzed the DNA methylation status on satellite I region in blastocysts obtained from cloned cattle. Embryos were produced by artificial insemination (AI) to non-cloned or cloned dams using semen from non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 35 publications
(43 reference statements)
2
25
0
Order By: Relevance
“…However, comparison of the methylation levels measured in SCNT blastocysts with those generated by IVF suggests that the seven day period from SCNT to blastocyst formation is either an insufficient period of time for complete reprogramming, or that SCNT embryos do not have the appropriate reprogramming factors to ensure that this repeat region is appropriately reprogrammed by the blastocyst stage. Similar findings have previously been reported in other repeat regions [10], [22]. Although the repeat region analyzed does not encode proteins, the transcription of non-coding RNAs from this sequence has been shown to play an integral role in maintaining chromatin in a specific conformation (review [18]) and aberrant RNA transcription of satellite sequences has been correlated with excessive DNA demethylation and genomic instability [23].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, comparison of the methylation levels measured in SCNT blastocysts with those generated by IVF suggests that the seven day period from SCNT to blastocyst formation is either an insufficient period of time for complete reprogramming, or that SCNT embryos do not have the appropriate reprogramming factors to ensure that this repeat region is appropriately reprogrammed by the blastocyst stage. Similar findings have previously been reported in other repeat regions [10], [22]. Although the repeat region analyzed does not encode proteins, the transcription of non-coding RNAs from this sequence has been shown to play an integral role in maintaining chromatin in a specific conformation (review [18]) and aberrant RNA transcription of satellite sequences has been correlated with excessive DNA demethylation and genomic instability [23].…”
Section: Discussionsupporting
confidence: 83%
“…Even if investigations are limited to a subset of epigenetic modifications such as DNA methylation, a broad spectrum of findings relating to the efficiency of epigenetic reprogramming following SCNT has been published. Varying combinations of hypo-methylation [1], [2], [3], [4], [5], [6], hyper-methylation [7], [8], [9], [10], mosaic methylation states [11] and normal methylation [8], [12], [13], [14], [15], [16], [17] following SCNT have been reported over the past decade. Direct comparison of these studies is problematic due to differences in analytical methods, genomic regions and tissue types investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Yamanaka et al . (2011) reported that high DNA methylation levels were found for the satellite I region in bovine fibroblasts used as donor cells [33]. Also, bovine cloned embryos at the blastocyst stage showed significantly higher DNA methylation levels than those of IVF embryos.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no significant difference in methylation levels between TSA-treated and untreated cloned embryos [8]. A previous report suggested that DNA hypermethylation of the satellite I region in cloned embryos was caused by cloning procedures, not the in vitro embryo culture procedure [33]. The higher methylation level of the satellite I region in cloned embryos compared with IVF embryos suggests that reprogramming of donor nuclei was uncompleted, and this likely contributed to low cloning efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it seems that satellite sequences in particular could be considered as possible candidates to target methylation and hydroxymethylation changes when comparing Day-7 to Day-12 bovine embryos. A previous comparison of methylation levels of repetitive loci during bovine development revealed that satellites I and II are hypo-methylated in blastocysts [53], consistently with studies hypothesizing that satellite demethylation occurs very early in the germ cell lineage, prior to entry into meiosis [54]. Given the hypothetical role of hydroxymethylation in oxidative demethylation, the increase in hydroxymethylation of bovine satellite sequences observed in HMe-RDA between Day-7 (13.9%) and Day-12 (25.2%) would be consistent with methylation removal associated with the differentiation of primordial germ cells in the early embryo genome which begins to happen in elongated bovine embryos [2].…”
Section: Discussionmentioning
confidence: 99%